Effectiveness of Warm Compress Therapy in Reducing Menstrual Pain Among Adolescent Girls at Sehati Senior High School, Karawang - Ade Krisna Ginting; Euis Atikah; Rina Dwi Anggraeni; Anisa Sekar Kedaton; Delcy Regiana Putri (Jurnal Kesehatan dan Kedokteran, 2025)
Dysmenorrhea is one of the most common reproductive health problems experienced by adolescent girls and frequently interferes with daily activities, academic performance, and overall quality of life. Although pharmacological treatments are commonly used to manage menstrual pain, non-pharmacological approaches are increasingly recommended due to their safety, affordability, and minimal side effects. Warm compress therapy is a simple intervention that may reduce menstrual pain by improving blood circulation, relaxing muscles, and decreasing uterine spasms. This study aimed to analyze the effect of warm compress therapy on menstrual pain among adolescent girls at Sehati Senior High School, Karawang. This study employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. A total of 30 adolescent girls experiencing dysmenorrhea participated in the study. Menstrual pain intensity was assessed before and after the administration of warm compress therapy using a standardized pain measurement scale. Data were analyzed using descriptive statistics and a Paired Sample t-Test with a significance level of 0.05. The results showed that the mean menstrual pain score decreased from 6.8 before the intervention to 3.2 after the administration of warm compress therapy. Statistical analysis revealed a significant difference between pretest and posttest pain scores (p = 0.000), indicating that warm compress therapy effectively reduced menstrual pain among adolescent girls. The reduction in pain intensity is associated with improved local blood circulation, muscle relaxation, and decreased uterine contractions. The findings imply that warm compress therapy can be implemented as a safe, simple, inexpensive, and easily accessible intervention for managing dysmenorrhea among adolescents. The originality of this study lies in its evaluation of warm compress therapy within a secondary school setting using a quasi-experimental pretest–posttest approach and direct measurement of pain intensity. The study provides additional empirical evidence supporting the integration of non-pharmacological pain management strategies into adolescent reproductive health programs and school health services.